Evaluation of knowledge of risk factors and warning signs of stroke – An observational study among future health care professionals - Syed, Wajid; Qadhi, Omaimah A.; Barasheed, Amal; AlZahrani, Ebtesam; Basil A. Al-Rawi, Mahmood (Frontiers in Public Health, 2023)
Background and objective The role of healthcare professionals in society is unique since they are providers of health information and medication counseling to patients. Hence, this study aimed to evaluate Knowledge of Risk Factors and Warning Signs of Stroke among undergraduate health care Students (UHCS) at King Saud University (KSU), Riyadh, Saudi Arabia. Methodology An online cross-sectional study was conducted among UHCS at KSU, Riyadh, Saudi Arabia from September to November 2022, using self-administered 34-item questionnaires divided into five sections to assess participants' knowledge of stroke risk factors, warning signs, and management and source of information about the stroke. The Statistical Package for the Social Sciences version 26 was used to analyze the data (SPSS). Results Of the 300 questionnaires distributed, 205 students completed the questionnaires, giving a response rate of 68.3%. Of whom 63 (30.7%) were pharmacy, 81 (39.5%) were nursing and 61 (29.8%) were emergency medical services (EMS) Students. One hundred and eighty-two (88.8%) of the students agreed that stroke affects bodily movement. With regards to risk factors, students identified high blood pressure 182 (88.8%), followed by heart disease 175 (85.4%), advanced age 164 (80%), previous Stroke history 158(77.1%), and lack of physical activity 156 (76.1%). Difficulty in speaking or slurred speech 164 (80%), dizziness, and loss of balance 163 (79.5%) were identified as the warning signs of stroke. In this study, 41.3 % of the pharmacy students reported a good level of knowledge than nursing and EMS students. However, 32.2% (N = 66) of the healthcare undergraduates reported good knowledge. The knowledge score was significantly associated with the year of study, and educational degree (p = 0.0001). Furthermore, there were no differences between parents working in healthcare settings (p = 0.99). Conclusion In conclusion, the knowledge of stroke among healthcare students at King Saud University varied. The reported knowledge gap mostly relates to stroke risk factors and warning signs. Therefore, increasing public awareness of potential risk factors and stroke warning signs needs to receive more attention.